DINAMIKA IMPLEMENTASI GOOD HOSPITAL GOVERNANCE DAN PRINSIP ETIKA AUTONOMI, BENEFICIENCE, NON-MALEFICENE & JUSTICE PADA KEPUTUSAN PELAYANAN PASIEN RUMAH SAKIT - Zia’ul Fatwa Andini Yusuf; Ade Supriatini; Uli Wildan Nuryanto (Universitas Bina Bangsa, 2022)
According to Riskesdas data in 2010 in Indonesia, the rate of cesarean delivery was 15.3%, the lowest was in Southeast Sulawesi 5.5% and the highest was in DKI Jakarta 27.2%. However, the trend in private hospitals in Surabaya reported that the number of CS deliveries continued to increase, in 2000 it was 47.2% and in 2005 it was 51.6%. Research conducted at the Lebak Hospital in 2011 reported that SC had a percentage of 63.4%. The high incidence of CS is not all based on medical indications but is now at the request of the patients themselves such as beautiful selection and related to social, economic, race, and health status. SC deliveries have higher costs compared to normal deliveries, resulting in high profitability for the hospital. Although according to the Healthcare Organization that the main goal of the hospital is profit. According to the Indonesian Medical Obstetrics and Gynecology Association, the asymptomatic patient is not to be blamed for a cesarean delivery, however, according to the Indonesian medical code of ethics, a doctor needs to consider all risks and complications that will occur to both the mother and the baby. This is in accordance with the principles of biomedical ethics which consist of four principles, including the principle of autonomy, the principle of beneficence, the principle of non-maleficence and the principle of justice. All principles and rules relating to the fulfillment of rules on hospital management have been very clearly regulated in Good Hospital Governance as guidelines for good hospital governance as well as a form of implementation in improving and providing health services to achieve national health goals